Introduction to special issue: Learning assessments for sustainability? Exploring the interaction between two global movements - Pizmony-Levy, Oren; Gan, Dafna (Education Policy Analysis Archives, 2021)
The aim of this special issue, “Learning Assessments for Sustainability?”, is to examine the interaction between the environmental and sustainability education (ESE) movement and the international large-scale assessments (ILSAs) movement. Both global educational movements emerged in the 1960s and their simultaneous work have affected each other since then. While the articles in this special issue highlight the potential benefits of ILSAs as a source of data for secondary analysis, they also demonstrate the limitations of ILSAs and their negative consequences to ESE. As such, we call for more research on the interaction between ESE and ILSAs and for a serious consideration of how test-based accountability practices might work against meaningful engagement with ESE. This introductory article includes three sections. The first section provides context about the movements. The second section presents an overview of the articles and alternative ways for reading them. The third section discusses lessons learned from the collection of articles. We conclude with a call for further research and reflection.